A Study on Merger and Operating Performance of Commercial Banks of Nepal - Dwa, Sajena; Shah, Ajay Kumar (Journal of Business and Social Sciences Research, 2018)
This study aims to find the impact of mergers on operating performance of sample merged banks. To attain the research objective, this study has taken 8 independent variables; operating profit margin, net profit margin, return on assets, return on equity, debt equity ratio, return on loan loss provision, return on staff expenses and return on operating expenses. Three cases have been taken for the study as a sample to examine whether merger has led to a profitable situation or not. Research mainly focuses on quarterly secondary data which is analyzed using paired sample t-test, correlation analysis, VIF test and regression analysis. From the analysis it is deduced that merger has no significant role in case of Nepal Bangladesh Bank and NIC Asia Bank in terms of various operational ratios, since many operational ratios have been found weaker in post-merger period than pre-merger period. But merger plays a significant role in case of Machhapuchchhre Bank where almost all operational ratios have improved in post-merger. While analyzing the situation of overall commercial banking sectors, with the help of sampled data, it is observed that largely the merger isn’t able to produce positive results for the merged entities. The study shows the reason for negative result of merger as the poor financial position of the target banks. Further the merger will somewhat act as a solution for the current problems of Nepalese BFIs. Merger will be a wise option to bring BFIs in strong and growing position and to meet the requirement of current paid up capital as per the latest NRB directive. But it also must be considered that merger in itself is not the ultimate solution to strengthen the financial position of BFIs. A lot of factors must be taken into account before finding the right partner to merge with and executing the merger. Journal of Business and Social Sciences Research, Vol. 2, No. 1 & 2, pp. 85-107